2016
DOI: 10.1103/physrevb.94.045311
|View full text |Cite
|
Sign up to set email alerts
|

Transferable tight-binding model for strained group IV and III-V materials and heterostructures

Abstract: It is critical to capture the effect due to strain and material interface for device level transistor modeling. We introduced a transferable sp3d5s* tight binding model with nearest neighbor interactions for arbitrarily strained group IV and III-V materials. The tight binding model is parameterized with respect to Hybrid functional(HSE06) calculations for varieties of strained systems. The tight binding calculations of ultra small superlattices formed by group IV and group III-V materials show good agreement w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 43 publications
3
50
0
Order By: Relevance
“…Foulkes and Haydock showed that the tight-binding approximation emerges as a stationary solution to density functional theory [21], which has provided a solid foundation to improve the accuracy of the tight-binding scheme. Environment-dependent tightbinding models, capturing the essential features of charge transfer and local environmental dependence of overlap integrals (e.g., to reproduce lattice deformations under strain [22]), have further improved the transferability and robustness of the tight-binding approach [18,[23][24][25][26].A key feature of the real-space empirical tight-binding (ETB) approach is its versatility. It can accommodate disorder, strain, magnetic interactions and external perturbations, and, as such, provides a particularly attractive framework to tackle realistic non-equilibrium device conditions in nanosystems and mesoscopic structures [27].…”
mentioning
confidence: 99%
“…Foulkes and Haydock showed that the tight-binding approximation emerges as a stationary solution to density functional theory [21], which has provided a solid foundation to improve the accuracy of the tight-binding scheme. Environment-dependent tightbinding models, capturing the essential features of charge transfer and local environmental dependence of overlap integrals (e.g., to reproduce lattice deformations under strain [22]), have further improved the transferability and robustness of the tight-binding approach [18,[23][24][25][26].A key feature of the real-space empirical tight-binding (ETB) approach is its versatility. It can accommodate disorder, strain, magnetic interactions and external perturbations, and, as such, provides a particularly attractive framework to tackle realistic non-equilibrium device conditions in nanosystems and mesoscopic structures [27].…”
mentioning
confidence: 99%
“…However, this simple TB model fails to reproduce some important band structure features, such as bandgap nature for indirect semiconductors [3,7]. Although the introduction of additional unphysical parameters can cure the flaw of the simple sp 3 TB model [8][9][10][11], it loses the advantage of its intuitive simplicity and thus is unlikely to uncover the origin of the direct and indirect bandgap natures of semiconductors. The poor understanding impedes the design of new direct bandgap light-emitting materials.…”
mentioning
confidence: 99%
“…Here, we reveal that the occupied cation d bands, which were neglected in previous models of the TB approach [6][7][8][9][10][11], play a prime role in forming the direct bandgap of We at first examine the nature of bandgaps of all conventional group-IV elemental, and group III-V and group II-VI compound semiconductors, which are the semiconductors of practical interest for information technology [3,5,23]. Fig.…”
mentioning
confidence: 99%
“…assuming linear alloy scaling. The tight‐binding parameters are fitted against bulk DFT calculations using VASP with the HSE06 potentials. The growth direction is the c‐plane and the Wurtzite crystal structure is explicitly represented in this atomistic basis.…”
Section: Methodsmentioning
confidence: 99%